2021
DOI: 10.1021/acs.est.1c04593
|View full text |Cite
|
Sign up to set email alerts
|

Upscaling of Denitrification Rates from Point to Catchment Scales for Modeling of Nitrate Transport and Retention

Abstract: The spatial and temporal variability of denitrification makes it challenging to integrate conceptual, process-based understandings of nitrate transport and retention into numerical modeling at the catchment scale, although it is critical for the realism and predictive power of the model. In this study, we propose a novel approach where the conceptual understandings of the spatial structure of denitrification zones and the corresponding representative denitrification rates are transformed into a form that can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
(129 reference statements)
1
5
0
Order By: Relevance
“…These lower concentrations suggest a greater extent of denitrification associated with low-redox conditions in the subsurface at these sampling locations. Similar evidence for patchiness and "hotspots" of denitrification in the subsurface, including riparian settings, has been reported previously (e.g., Gold et al, 1998;Kim et al, 2021).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…These lower concentrations suggest a greater extent of denitrification associated with low-redox conditions in the subsurface at these sampling locations. Similar evidence for patchiness and "hotspots" of denitrification in the subsurface, including riparian settings, has been reported previously (e.g., Gold et al, 1998;Kim et al, 2021).…”
supporting
confidence: 85%
“…These isotope results also support the concept of short‐circuiting (“bypass”) via preferential pathways in the riparian zones. In addition to large variations in nutrient concentrations in shallow riparian groundwater (Table 3, Figure 9), we note that the shallow subsurface is characterized by heterogeneity of hydraulic properties (Cey et al, 1998; Van Stempvoort et al, 2021) and rates of biogeochemical processes (e.g., Carlyle & Hill, 2001; Kim et al, 2021). These considerations reinforce the reasonableness of our approach to use BF EE samples instead of sparse groundwater data to infer catchment‐wide fluxes of solutes from groundwater to our study streams.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the full range of rates reported for riparian sites in sand terrain (38%-99%) overlapped with the sparse available results for till terrain sites (50%-60%). In contrast, Kim et al (2022) reported complex spatial distribution of denitrification rates in an agricultural catchment in Denmark, where the shallow subsurface included various till units and meltwater sediments, largely sands and silts. They reported that denitrification rates in the saturated zone varied by more than four orders of magnitude, and decreased with increasing depth, but found no significant differences in denitrification rates related to redox conditions or lithology.…”
Section: Relationships Between Stream Nitrate Concentrations Land Cov...mentioning
confidence: 94%
“…The denitrification rates in the anoxic nitrate reducing zone and the reduced zone are determined in the laboratory using the core samples collected from the study catchment by the acetylene-blockage method 54 . In oxic zones, where denitrification is assumed to be negligible, the denitrification rate is set to zero 55 .…”
Section: Methodsmentioning
confidence: 99%